Examining Negative Emotional Symptoms and Psychological Wellbeing of Australian Sport Officials - Carson, Fraser (Int J Environ Res Public Health, 2020)
Sports officials are exposed to numerous performance and personal stressors, however little is known about their mental health and psychological wellbeing. This study investigated levels of mental health and psychological wellbeing of sports officials in Australia, and the demographic, officiating, and workplace factors associated with these outcomes. An online survey consisting of demographic and officiating questions, and measures of work engagement, mental health and psychological wellbeing was completed by 317 officials. A negative emotional symptoms score was computed. Associations between key demographic, officiating, and workplace factors with negative emotional symptoms and psychological wellbeing were assessed using univariate and multivariate analyses. Officials who were younger, not in a committed relationship, having lower levels of education, and less officiating experience reported higher levels of negative emotional symptoms, while males, older than 50 years, in a committed relationship and more officiating experience had higher levels of psychological wellbeing. The ability to self-manage workload and demonstrate professional autonomy were strongly associated with negative emotional symptoms and psychological wellbeing. Officials reported high negative emotional symptoms, but also high levels of psychological wellbeing. The ability to manage workload and to express professional autonomy are important determinants of mental health and wellbeing levels of sports officials.